Efficacy and Safety Profile of Histone Deacetylase Inhibitors for Metastatic Breast Cancer: A Meta-Analysis - Wang, Changjun; Lin, Yan; Zhu, Hanjiang; Zhou, Yidong; Mao, Feng; Huang, Xin; Sun, Qiang; Li, Chenggang (Frontiers in Oncology, 2022)
Introduction: Acquired resistance to endocrine therapy (ET) remains a big challenge in management of metastatic breast cancer (MBC). Novel therapeutic agent, histone deacetylases inhibitors (HDACi), targets the abnormal epigenetic modification and may overcome acquired resistance. However, there remains controversy on HDACi efficacy and safety profile for hormone receptor (HoR) positive /Human epidermal growth factor receptor 2 (HER2) negative MBC. Methods: Two independent reviewers searched Pubmed, Embase and Cochrane Central Register of Controlled Trials databases for relevant studies on HDACi and HoR+/HER2- MBC. Demographic and clinicopathological parameters were extracted and presented as means and proportions, and between-group differences were assessed by Pearson Chi-square test. Fixed or random effect models were used for meta-analysis based on inter-study heterogeneity. Pooled results were presented as L'Abbé plot and forest plot. Funnel plot and Egger’s test were employed for evaluation of publication bias. Results: Four studies with 1457 patients were included for meta-analysis. The overall objective response rates (ORR) of HDACi + ET (HE) and Placebo + ET (PE) groups were 11.52% and 6.67%, respectively. HE regimen significantly increased ORR (odds ratio [OR] 1.633, 95% confidence interval [CI] = 1.103-2.418, p < 0.05), and showed higher clinical benefit rate (CBR) than PE regimen (HE Vs. PE groups: 38.82% Vs. 30.58%, OR 1.378, 95% CI = 1.020-1.861, p < 0.05). Additionally, HE regimen associated with prolonged progression-free survival (PFS) (hazard ratio [HR] 0.761, 95% CI = 0.650 – 0.872, p < 0.001) and overall survival (OS) (HR 0.849, 95% CI = 0.702 – 0.996, p < 0.001). Regarding safety profile, HE regimen had increasing toxicity in terms of higher overall adverse event (AE), Grade ≥3 AE, dose modification and discontinuation rate. Conclusions: This meta-analysis validated that HE regimen had superior efficacy over control in terms of ORR, CBR, PFS and OS, but accompanied with increasing toxicity. HDACi plus ET could serve as an important option in managing HoR+/HER2- MBC. Future studies may focus on the clinical difference among different HDACi and AE managements to enhance tolerability.